ERECTILE DYSFUNCTION AFTER TRANSURETHRAL PROSTATE RESECTION (TURP) IN PATIENTS WITH LOWER URINARY TRACT SYMPTOMS AT KOJA HOSPITAL, JAKARTA - Huseini, Maruto Harjanggi; Sutarto, Waluyo Eko (Indonesian Urological Association, 2021)
Objective: Aim of this study is to identify risk factors associated with erectile dysfunction in post-transurethral prostate resection (TURP) patients for the management of benign prostatic hyperplasia (BPH). Material & Methods: During 2019, 22 patients met the TURP indication criteria in the urology polyclinic of Koja Hospital for symptomatic BPH management. All patients underwent transabdominal ultrasonography to confirm prostate volume and underwent laboratory tests to measure serum prostate-specific antigen (PSA). History of comorbidities such as diabetes mellitus, cardiovascular events, and hypertension was recorded. The patient's sexual function was determined using the International Index of Erectile Function questionnaire (IIEF-5) before surgery and six months postoperatively, where erectile dysfunction was established for scores below 21. Mean comparisons were made to see if there was a significant change in IIEF score six months postoperatively. Results: There were 22 subjects as samples with a mean age of 63 ± 3.8 years, prostate volume 47.64 ± 5.5 mL and a median PSA level of 3.3 [1-47] ng/dL. The comorbidities found in the subjects were diabetes mellitus (22.7%), cardiovascular events (36.4%), and hypertension (27.3%). The mean IIEF-5 score before surgery was 14.55 ± 0.78 and was not significantly different (p= 0.225) with a reevaluation six months after surgery of 14.18 ± 0.76. Conclusion: There was no change in the severity of erectile dysfunction in patients undergoing TURP surgery.